Scientists Develop Precision Maps for Other Planets. (26th March 2013) - Kumar, Mohi
Abstract : Earth and planetary scientists are united by their need for accurate maps. Without them, features studied have no reference point, attempts to understand how our and other planets evolved have no context, and missions flown to other planets lack purpose. "Making maps out of data is critical to further progress in our fields, " explained Randolph Kirk of the U.S. Geological Survey's (USGS) Astrogeology Science Center, based in Flagstaff, Ariz. "Building maps helps other people find what's out there."